Development of a Novel Religious Addiction Scale Pilot Study - Uzoigwe, Tobechi (International Journal of Educational and Psychological Sciences, 2024)
This study sought  to develop a religion addiction scale using a cross-sectional design with 74 participants from an online WhatsApp group. The analysis showed that most items met the .30 correlation value requirement, indicating high reliability. The scale demonstrated high internal consistency (Cronbach alpha = .97), making it a reliable tool for assessing religious addiction. Results showed that younger participants were more likely to exhibit religious addiction, while gender and religious affiliation did not significantly impact scores. Muslims had slightly higher scores than Christians, but the difference was not statistically significant. The study recommends using this scale to measure religious addiction, providing a valuable tool for researchers and clinicians.